SISTEM PAKAR DIAGNOSA KERUSAKAN PADA MOTOR MATIC VARIO BERBASIS WEB - Imam Wicaksono; Fitro Nur Hakim; Victor Gayuh Utomo (Jurnal Transformatika, 2016)
Vario matic motorcycle riders do not know the constraints Vario matic motor damage and tend to leave the constraints of damage to the mechanical motor matic Vario without knowing that the actual damage is a simple damage, but if the rider had knowledge of treatment damages the motor matic Vario Vario matic handling damage can be done solely by the rider so that handling damage can be handled immediately without having to wait for a motorcycle repaired in the workshop. This study aims to produce rules as a knowledge base for damage matic based on the symptoms of damage and produce an expert system for diagnosis of the motor and electrical damage in the motor vehicle Vario matic. Methods in the design of this expert system uses an expert system dengen stages 6 stages, namely the identification, conceptualization, formalization, implementation, evaluation and development system. Diagnosis expert system Vario matic damage to the motor can be used to solve the problem of damage to motor matic vario diagnosis because it can give a diagnosis of any type of damage to the value of the probability of occurrence of each type of damage.